Characteristics of Purple Sweet Potato Yogurt and Its Effect on Lipid Profiles of Sprague Dawley Rats Fed with High Fat Diet - Lily Arsanti Lestari; Qisthira Swasti Amirina; Dina Septari Anindyah; Ainun Nisa; Annisa Nurul Huda; Widiyani Indrianingrum; Prasetyastuti; Nurliyani (Journal of Food and Pharmaceutical Sciences, 2020)
The objectives of this study were to evaluate the effect of purple sweet potato (PSP) yogurt on thelipid profile of Sprague Dawley rats. The PSP yogurt was made from fresh PSP (F-PSP) and its powder (P-PSP).The viscosity, pH, total titratable acid, proximate, antioxidant activity, anthocyanin content, and total lacticacid bacteria (LAB) between those yogurts were compared. Selected yogurt was given to Sprague Dawley ratsfor 4 weeks. Serum lipid profiles were determined after 2 and 4 weeks of treatment. F-PSP yogurt has betterphysical, chemical and microbiological properties compared to P-PSP yogurt. The serum cholesterol andtriglyceride levels in F-PSP yogurt group was not significantly different compared to control group (P>0.05).However, the reduction of serum LDL cholesterol in F-PSP yogurt group was significantly higher than controlgroup. The serum HDL cholesterol in the yogurt group decreased after 2 weeks of treatment, but it increasedafter 4 weeks of treatment. F-PSP yogurt could be used as an alternative functional food that could lower theblood cholesterol level because of the ability to reduce the LDL cholesterol level.